Analisis Perhitungan Harga Pokok Produksi Dengan Menggunakan Metode Full Costing Sebagai Dasar Penentuan Harga Produksi Rumah Panggung Pada CV Manguni Perkasa Kakaskasen Dua Tomohon - Gloria Tarek; Dolina L. Tampi; Dantje Keles (JURNAL ADMINISTRASI BISNIS, 2018)
The purpose of this study is to determine the calculation of the cost of production and the selling price of products  stilt houses and  gazebo at CV Manguni Perkasa. Calculation of cost of goods manufactured using the full costing methodThe type of research used in this study is quantitative research. The data used in this study are classified as quantitative descriptive research. The data used in this study are primary data obtained directly from the company such as data from interviews with the company and data in the form of information on the company's production costs for the manufacture of  and gaseboh stage house measuring . while for secondary data obtained from: books, journals, internet and other media that support this research. From the results of data analysis, the results of the study indicate that the calculation of the cost of production is lower than the cost of production by using the full costing method. The cost of production for stage house products for a size  is calculated using the company's method of Rp. 159,266,640 while according to the full costing method that is Rp. 170,276,640. while for gazebo products the cost of production is calculated using the company's method of Rp. 37,996,000. while using the full costing method of Rp. 48,996,000. this is because in the calculation of factory overhead, the company does not take into account several costs into the cost of production. Furthermore, in determining the selling price, the company only uses the method as it is then adds a profit of 30 percent of the total cost of production calculated.Keywords: Cost of production, full costing.